Keesaan YHWH dan Identitas Tritunggal: Kajian Teologi Biblika atas Kesinambungan Monoteisme Alkitabiah - Yustinus Yustinus (KARDIA: Jurnal Teologi dan Pendidikan Kristiani, 2026)
Abstract: In contemporary Christian theology, the divine identity of YHWH is often reduced to God the Father, resulting in a fragmented understanding of the relationship between Jesus Christ, the Holy Spirit, and the God of Israel. This article investigates YHWH as the single divine identity that grounds the unity of the Father, the Son, and the Spirit within the canonical witness of Scripture. Employing a biblical-theological approach, the study conducts a layered textual analysis of key Old and New Testament passages, including Exodus 3:14–15, Deuteronomy 6:4, Joel 2:28–32, Romans 10:9–13, Philippians 2:9–11, 1 Corinthians 8:6, John 1:1–3, and Hebrews 1:10–12. The findings demonstrate that the oneness of YHWH in the Old Testament functions as a covenantal identity claim rooted in creation and redemptive action. The New Testament consistently applies texts, attributes, and prerogatives of YHWH to Jesus Christ without abandoning Jewish monotheism. The term “single” in the title, therefore, denotes the indivisible unity of divine identity rather than a denial of personal distinction. This study argues that the doctrine of the Trinity represents a canonical articulation of YHWH’s unified and relational identity, firmly grounded in biblical monotheism. Abstrak: Dalam praktik iman Kristen kontemporer, identitas ilahi YHWH sering direduksi hanya kepada Allah Bapa, sehingga relasi Yesus Kristus dan Roh Kudus dengan YHWH Perjanjian Lama tidak terbaca secara utuh. Artikel ini mengkaji YHWH sebagai identitas ilahi tunggal yang menjadi dasar kesatuan Bapa, Putera, dan Roh Kudus dalam kesaksian kanonik. Penelitian menggunakan pendekatan teologi biblika dengan analisis berlapis terhadap teks-teks kunci Perjanjian Lama dan Perjanjian Baru, khususnya Keluaran 3:14–15, Ulangan 6:4, Yoel 2:28–32, Roma 10:9–13, Filipi 2:9–11, 1 Korintus 8:6, Yohanes 1:1–3, dan Ibrani 1:10–12. Hasil penelitian menunjukkan bahwa keesaan YHWH dalam Perjanjian Lama merupakan klaim identitas perjanjian yang konsisten, dan Perjanjian Baru secara sistematis menerapkan teks, atribut, dan prerogatif YHWH kepada Yesus tanpa membatalkan monoteisme Israel. Istilah “tunggal” dalam judul karena itu menunjuk pada kesatuan identitas ilahi yang tidak terbagi, bukan pada penolakan terhadap pembedaan personal. Artikel ini menegaskan bahwa doktrin Tritunggal merupakan artikulasi kanonik atas identitas YHWH yang esa dan relasional dalam kesinambungan monoteisme alkitabiah.